2010
DOI: 10.1089/end.2009.0482
|View full text |Cite
|
Sign up to set email alerts
|

Prospects in Percutaneous Ablative Targeting: Comparison of a Computer-Assisted Navigation System and the AcuBot Robotic System

Abstract: Aim: Precise targeting is essential for adequate treatment of lesions during image-guided therapy. The aim of this study was to compare the performance of two emerging image-guided targeting technologies in a phantom model. Materials and Methods: A computer-assisted navigation system and AcuBot were tested using three operators: an interventional radiologist and two endourologists. Fiducials were placed in an anatomic gelatin phantom and targeted by both systems. The images were reconstructed and analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 11 publications
0
28
0
1
Order By: Relevance
“…4) [(www.clearguidemedical.com/news) 30 August 2015]. The company is a Johns-Hopkins University spin-off, trying to commercialize products of previous projects [7,8]. Until now, there are no publications in urology.…”
Section: Electromagnetic Tracking For Puncturementioning
confidence: 99%
“…4) [(www.clearguidemedical.com/news) 30 August 2015]. The company is a Johns-Hopkins University spin-off, trying to commercialize products of previous projects [7,8]. Until now, there are no publications in urology.…”
Section: Electromagnetic Tracking For Puncturementioning
confidence: 99%
“…It has also been suggested that the use of robotic assistance during needle placement can help minimize the radiation exposure to operators and patients during CT or fluoroscopy guided interventional procedures [17; 2027]. At the same time, the use of robotic guidance may also reduce the number of needle adjustments required to reach a target, thereby reducing patient complications such as bleeding[28]. …”
Section: Introductionmentioning
confidence: 99%
“…With specialized hardware adjustment in Acubo-RND, the dependency on novice can be reduced leading to lower placement error. According to other studies with PPI-BT robots, sub-millimeter precision is possible [10,32,33].…”
Section: Discussionmentioning
confidence: 93%
“…Some of these brachytherapy-specific devices can insert needles at a continuum of locations and angles, emulating the degrees of freedom provided by freehand techniques, but can also place the tip of a needle with millimeter accuracy. However, the majority of current brachytherapy robot prototypes focus on PPI-BT [27,28,29,30,31], including the Acubot-RND [10,32,33], which is a needle insertion robot with applications to PPI-BT. Fig.…”
Section: Background and Related Workmentioning
confidence: 99%